Attachment-based compassion therapy and adapted mindfulness-based stress reduction for the treatment of depressive, anxious and adjustment disorders in mental health settings: a randomised controlled clinical trial protocol - Jesus Montero-Marin; Carlos Collado-Navarro; Mayte Navarro-Gil; Alba Lopez-Montoyo; Marcelo Demarzo; Paola Herrera-Mercadal; Alberto Barcelo-Soler; Javier Garcia-Campayo (BMJ Open)
Introduction Depressive, anxiety and adjustment disorders are highly prevalent among mental health outpatients. The lack of funding for mental health problems produces inefficient results and a high burden of disease. New cost-effective group interventions aimed at treating these symptoms might be an appropriate solution to reduce the healthcare burden in mental health units. Mindfulness-based interventions (MBIs) have shown significant reductions in anxious, depressive and adjustment symptomatology. Recent research highlights the influence of compassion as a key mechanism of change. However, MBIs only address compassion implicitly, whereas compassion-based protocols consider it a core aspect of psychotherapy. In this randomised controlled trial, we hypothesise that the provision of attachment-based compassion therapy (ABCT), which is a compassion-based protocol, will be more effective than mindfulness-based stress reduction (MBSR), which is a conventional MBI programme, for the treatment of depressive, anxious and adaptive symptoms in patients in mental health settings.Methods and analysis Approximately 90 patients suffering from depressive, anxious or adjustment disorders recruited from Spanish mental health settings will be randomised to receive 8 weekly 2 hours group sessions of ABCT, 8 weekly 2.5 hours group sessions of adapted MBSR (with no full-day silent retreat) or treatment as usual (TAU), with a 1:1:1 allocation rate. Patients in the ABCT and adapted MBSR groups will also receive TAU. The main outcome will be general affective distress measured by means of the ‘Depression Anxiety Stress Scales-21’ at post-test as primary endpoint. Other outcomes will be quality of life, mindfulness, self-compassion and the use of healthcare services. There will be a 6-month follow-up assessment. Intention-to-treat analysis will be conducted using linear mixed models. Per-protocol and secondary outcome analyses will be performed. A data monitoring committee comprising the trial manager, the ABCT and MBSR teachers and an independent clinical psychologist will monitor for possible negative side effects.Ethics and dissemination Approval was obtained from the Ethics Committee of the General University Hospital of Castellón, Spain. The results will be submitted to peer-reviewed specialised journals, and brief reports will be sent to participants on request.Trial registration number NCT03425487